Brief Report: Exercise and Anxiety in Adults with Arthritis and Other Rheumatic Diseases: Support for Evidential Value. (18th October 2018) - Kelley, George A.; Kelley, Kristi S.; Callahan, Leigh F.
Abstract : Objective . Given the high prevalence of anxiety in adults with arthritis and other rheumatic diseases (AORD) and the subsequent need for interventions to reduce anxiety, this brief report sought to determine if evidential value exists to support the role of exercise for reducing anxiety in adults with AORD. Methods . Utilizing data from a prior meta-analysis, a recently developed approach, P -curve, was used to determine evidential value by assessing for publication bias and p -hacking . Binomial tests as well as the more robust Stouffer's test were used to examine for evidential value. To examine the influence of selected studies on p- curve results, findings were also examined by dropping the highest and lowest p values from the analysis. Results . The binomial test for evidential value was not statistically significant ( p = 0.11) while the more robust Stouffer's test satisfied both conditions for evidential value ( p = 0.002). Power analyses suggested a good fit for the observed p -curve. Results were generally robust when the least and most extreme values were excluded. Conclusions . The results of this study provide evidential support for the benefits of exercise on anxiety in adults with AORD.